Evaluation of the Preventive Effects of Fish Oil and Sunflower Seed Oil on the Pathophysiology of Sepsis in Endotoxemic Rats - Kuo, Yen-Shou; Hu, Mei-Hua; Chan, Wei-Hung; Huang, Tien-Yu; Chou, Yu-Ching; Huang, Go-Shine (Frontiers in Nutrition, 2022)
Sepsis causes platelet activation, systemic inflammation, organ dysfunction, and mortality. Endotoxins play an important role in the manifestation of the symptoms of septic shock. As fish oil exert well known anti-inflammatory effects and sunflower seed oil exert less anti-inflammatory properties than fish oil, both oils are widely used. We aimed to test the hypothesis that dietary supplementation of these two oils before endotoxemia modulates the consequences of illness. Nine- to ten-week-old male Wistar rats (N = 55) were divided into four groups: group A (N = 6), control; group B (N = 17), saline + lipopolysaccharide (endotoxin); group C (N = 17), fish oil + lipopolysaccharide; and group D (N = 15), sunflower seed oil + lipopolysaccharide. After 28 days of feeding the designated diet, the rats in all groups were intraperitoneally injected with lipopolysaccharide. After 24 h, survival rate, endotoxemia severity, levels of platelet activation markers, organ function and biochemical variables were evaluated. Platelet-leukocyte aggregation was significantly high in group C (p = 0.005), and platelet-monocyte aggregation was significantly high in groups C (p = 0.003) and D (p = 0.016) than in group B. The survival rate, endotoxemia severity, expression of platelet P-selectin, CD40L, and TLR4, pulmonary function, renal function, liver function, or biochemical variables did not significantly differ among groups B, C, and D. Instead of an anti-inflammatory effect, the dietary supplementation of fish and sunflower seed oils exerted a pro-inflammatory effect, especially via platelet-monocyte aggregation, suggesting a rebound effect of the dietary supplementation of the oils. The oils did not affect other inflammatory platelet markers or improve the outcome of endotoxemic rats. However, further studies are required to understand the underlying mechanisms of such effects and to elaborate the clinical significance of these findings.